Representation of movement-based integrated learning in different physical environments of an early education institution - Vujičić, Lidija (Revija za elementarno izobraževanje, 2020)
The aim of this paper is to determine the differences in the representation of children's integrated learning in an institutional context between standard children's integrated learning and movement'based integrated learning. The research encompasses two early-aged children's groups attending city kindergartens. The content analysis method was used; activities were photographed and filmed with video cameras. Movementbased integrated learning has a significant influence on the quality of the educational process.
Keywords: early-aged children; educational process; fizično okolje; gibanje; hipotetične naloge učitelja; integrated learning; integrirano učenje; mlajši predšolski otroci; movement; physical environment; vzgojni proces